Systematic correlations of the earthquake frequency‐magnitude distribution with the deformation and mechanical regimes in the Taiwan orogen - Yen‐Ling Chen; Shu‐Huei Hung; Juen‐Shi Jiang; Ling‐Yun Chiao (Geophysical Research Letters)
Abstract We investigate the correlation of the earthquake frequency‐magnitude distribution with the style of faulting and stress in Taiwan. The b values estimated for three types of focal mechanisms show significant differences with the lowest for thrust, intermediate for strike slip, and highest value for normal events, consistent with those found in global and other regional seismicity. Lateral distribution of the b values shows a good correlation with the predominant faulting mechanism, crustal deformation, and stress patterns. The two N‐S striking thrust zones in western and eastern Taiwan under the larger E‐W shortening and differential stress yield the lower b values than those in the in‐between mountain ranges subject to the smaller extensional stress and dominated by strike slip and normal faults. The termination of the monotonically decreasing b value with depth at ~15–20 km corroborates its inverse relationship with stress and the existence of the brittle‐plastic transition in the weak middle crust beneath the Taiwan orogen.